Cryptosporangium phraense sp. nov., isolated from plant litter. Issue 2 (14th November 2019) - Suriyachadkun, Chanwit; Ngaemthao, Wipaporn; Pujchakarn, Tawanmol; Chunhametha, Suwanee
Abstract : A novel zoosporic actinomycete, designated strain A-T 5661 T, was isolated from plant litter collected in Thailand. Strain A-T 5661 T developed large multilocular sporangia containing motile sporangiospores at the ends of sporangiophores on substrate mycelium. The results of our polyphasic taxonomic study demonstrated that the strain had characteristics typical of members of the genus Cryptosporangium . The 16S rRNA gene sequence and phylogenetic analyses indicated that strain A-T 5661 T shared the sequence similarity ≤98.5 % with all members of the genus Cryptosporangium . The values of DNA–DNA relatedness that distinguished this novel strain from its closest related species were below 70 %. The cell-wall peptidoglycan contained meso -diaminopimelic acid. The whole-cell sugars were acofriose, arabinose, galactose, glucose, mannose, xylose and ribose. The predominant menaquinones were MK-9(H8 ) and MK-9(H6 ) with minor amounts of MK-9(H4 ) and MK-9(H2 ). The predominant fatty acids were iso-C16 : 0, C18 : 1 ω9 c and anteiso-C17 : 0 . The polar lipid profile consisted of phosphatidylethanolamine, diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol, phosphatidylinositol mannosides and unidentified polar lipids. The G+C content of the genomic DNA was 71.6 mol%. Based on comparative analysis of phenotypic, chemotaxonomic and genotypic data, the novel zoosporic actinomycete A-T 5661 T (=TBRC 8127 T =NBRC 113237 T ) is proposed to be the type strain of a novel species, Cryptosporangium phraense sp. nov.